The New Cultural Conflict, Polarization, and Representation in the Swiss Party System, 1975–2011. Issue 4 (30th October 2015) - Bornschier, Simon
Abstract: Party relationships in the Swiss party system have become substantially more antagonistic over the past decades. This article analyzes the actors and ideologies that have triggered the emergence of a polarizing cultural antagonism, and shows that this conflict is not primarily about Switzerland's relationship with Europe. The implications of the emergence of the new cultural conflict for democracy are far from clear. Using an innovative approach to measure the congruence between voter preferences and party positions, I show that the representation of citizens' interests along the cultural dimension has improved significantly since the 1970s. The concomitant polarization of the economic dimension has not altered the quality of representation, on the other hand. I conclude by discussing the trade‐offs between the political articulation of a traditionalist‐communitarian conception of community that clearly resonates with an important part of the Swiss populace, and other components of liberal democracy.